2015
DOI: 10.5935/0004-2749.20150062
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in patients undergoing cataract surgery

Abstract: Approved by the following research ethics committee: Federal University of Paraná (UFPR), 654.007. ABSTRACT Purpose:To assess the ability of spectral domain optical coherence tomography (SD-OCT) to diagnose macular changes pre-and post-cataract surgery and to identify changes in central foveal thickness (CFT) relative to age, sex, and presence of concomitant ophthalmic pathologies, for a period of 6 months post-surgery. Methods: A prospective study of patients evaluated by SD-OCT within 5 h before surgery at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Moreira Neto et al . 12 investigated 98 patients undergoing cataract surgery; they diagnosed preoperative maculopathies in 21.4% of the patients with SD-OCT, which was a larger percentage than that detected with binocular indirect ophthalmoscopy (11.2%). In that study, patients with clinically detectable macular pathologies also were included.…”
Section: Discussionmentioning
confidence: 99%
“…Moreira Neto et al . 12 investigated 98 patients undergoing cataract surgery; they diagnosed preoperative maculopathies in 21.4% of the patients with SD-OCT, which was a larger percentage than that detected with binocular indirect ophthalmoscopy (11.2%). In that study, patients with clinically detectable macular pathologies also were included.…”
Section: Discussionmentioning
confidence: 99%
“…Bozkurt et al have shown that intracameral injection of 0.2 mL epinephrine (1:5,000) did not increase the risk of central macular edema in eyes with no risk factors that had uneventful phacoemulsification with intraocular lens implantation 39. However, patients with diabetes are prone to the development of macular edema postoperatively with the use of epinephrine 40,41. None of the patients in our study had developed macular edema at the 3-month follow-up.…”
Section: Discussionmentioning
confidence: 43%
“…Spectral-domain OCT (SD-OCT) is the gold standard for diagnosing many macular abnormalities, including vitreomacular interface disorders. 3 4 5 6 However, many clinics do not routinely perform preoperative macular OCTs before cataract surgery unless macular findings were observed during a standard examination. 5 …”
Section: Introductionmentioning
confidence: 99%